From sheet to screen: Teachers' needs for science literacy-based explanatory text writing learning in vocational schools - Sofia, Risnawati; Dadang S. Anshori; Halimah; Nurulrabihah Mat Noh (Journal of Applied Studies in Language, 2025)
This study aims to describe the profile and needs of teachers in learning to write science literacy-based explanatory texts at Vocational High Schools (SMK) in Cianjur, Jawa Barat. Employing a descriptive qualitative method, data were collected via an online questionnaire distributed to 19 Indonesian language teachers. The questionnaire instrument consisted of closed and open questions covering respondents' identity, teaching experience, learning challenges, and needs for teaching materials. The results show that most teachers, with varying teaching experience, have taught explanatory texts. However, learning still predominantly focuses on mechanical aspects and has not been optimally integrated with elements of science literacy. Conventional textbooks are still the primary source of learning, while utilizing digital media and contextual materials is minimal. Teachers also expressed the need for teaching materials linking text structures with scientific understanding relevant to students' lives. In addition, training for teachers in integrating science literacy into writing instruction is urgently needed. These findings confirm the importance of developing science literacy-based writing e-modules to solve classroom learning challenges and improve students' critical thinking, information literacy, and writing skills in a contextual and meaningful way.